2011
DOI: 10.1139/l11-087
|View full text |Cite
|
Sign up to set email alerts
|

Crack width model for thick reinforced concrete plates subjected to in-plane forces

Abstract: An extensive experimental program is conducted in the present study to investigate the cracking behavior of two normal strength concrete plates and thirteen high strength concrete plates. The results raise questions about the applicability of the present code approaches to predict the crack width of thick concrete plates used for offshore structures and containment structures for nuclear power plants. The main objective is to provide a simple equation for crack width prediction of a concrete plate to ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…The validity of code prescribed crack width and spacing computations have been studied extensively, and it has been found that code based computations can be modified for thick structural members, like the piers of the Rebecca Street Bridge. Thus, the Crack Width Model (Dawood and Marzouk, 2011) and Neural Analysis (Elshafey et al, 2013) will be utilized to compute the crack width and spacing respectively. In addition, the dynamic modulus of elasticity is computed using the shear wave velocities obtained for the piers and abutments during the scanning phase and are transformed into dynamic modulus of elasticity values using adopted models (Popovics et al, 2008;Birgul, 2009).…”
Section: Project Scopementioning
confidence: 99%
See 3 more Smart Citations
“…The validity of code prescribed crack width and spacing computations have been studied extensively, and it has been found that code based computations can be modified for thick structural members, like the piers of the Rebecca Street Bridge. Thus, the Crack Width Model (Dawood and Marzouk, 2011) and Neural Analysis (Elshafey et al, 2013) will be utilized to compute the crack width and spacing respectively. In addition, the dynamic modulus of elasticity is computed using the shear wave velocities obtained for the piers and abutments during the scanning phase and are transformed into dynamic modulus of elasticity values using adopted models (Popovics et al, 2008;Birgul, 2009).…”
Section: Project Scopementioning
confidence: 99%
“…Extensive research has been done in this field to attempt to study the cracking behavior of flexural reinforced concrete members (Clark, 1956;Frantz and Breen, 1980;Hwan and Jin, 1987;Frosch, 2002). A model for predicting the crack width along the length of the crack was adopted (Dawood and Marzouk, 2011). Therefore, the profile of the cracking opening along the length of the primary cracks can be developed.…”
Section: Crack Width Model For Thick Reinforced Concrete Membersmentioning
confidence: 99%
See 2 more Smart Citations
“…Bandymų ypatumas -tempimo apkrova elementams buvo perduodama "per betoną": bandymų schema ir daviklių išdėstymas parodytas 1.25 paveiksle. Dawood & Marzouk (2011) atliko plonų plokščių, tempiamųju dviem kryptimis, bandymus. Sukurta unikali bandymų įranga, leidžianti apkrauti elementus dviem ortogonaliomis kryptimis.…”
Section: Deformacijų Jutikliaiunclassified